Caesarean section: Frequency, indications and maternal and perinatal morbidity and mortality. Prospective study. - Alcántera Galarreta, R. (2015)
Six hundred forty three women who had a cesarean done at Belen´s Hospital from November 1991 to October 1992 were studied to determine frequency, indications and maternal and perinatal morbidity and mortality. Incidence was 16,6% of all deliveries. Most frequent indications were repeat cesarean section (32,8%), cephalopelvic disproportion (24,5%), breech presentation (10,7%) and pregnancy induced hypertension (10,4%). Thirty nine mother (6,06%) presented morbidity: endometritis in 15 cases, anemia in 11 and abdominal wall infection in 10. One mother died from hypovolemic shock caused by placenta previa. Morbidity in neonates (71,2%) consisted in more than one pathology. Infections ocurred in 315 newborn infants (70,6%), asphyxia in 105 (23,5%) and ictericia in 82 (18,3%). Twenty-one infants died in uterus and 20 newborns died. Causes of neonatal deaths were asphyxia in 15, acute rapiratory distress in 13 and sepsis in 12. Perinatal mortality rate was 52,9% x 1000 l.b. An adequate deliveg management decrease the incidence of maternal and perinatal morbidity and mortality of cesarean section.